Experimental Validation of a Computational Fluid Dynamics Methodology for Transitional Flow Heat Transfer Characteristics of a Steady Impinging Jet - PERSOONS, TIM; MURRAY, DARINA (My University, 2014)
This paper presents a computational fluid dynamics (CFD) methodology to accurately predict the heat transfer characteristics of an unconfined steady impinging air jet in the transitional flow regime, impinging on a planar constant-temperature surface. The CFD methodology is validated using detailed experimental measurements of the local surface heat transfer coefficient. The numerical model employs a transitional turbulence model which captures the laminar–turbulent transition in the wall jet which precisely predicts the intensity and extent of the secondary peak in the radial Nusselt number distribution. The paper proposes a computationally low-cost turbulence model which yields the most accurate results for a wide range of operating and geometrical conditions. A detailed analysis of the effect of mesh grid size and properties, inflow conditions, turbulence model, and turbulent Prandtl number Prt is presented. The numerical uncertainty is quantified by the grid convergence index (GCI) method. In the range of Reynolds number 6000 ≤ Re ≤ 14,000 and nozzle-to-surface distance 1 ≤ H/D ≤ 6, the model is in excellent agreement with the experimental data. For the case of H/D = 1 and Re = 14,000, the maximum deviations are 5%, 3%, and 2% in terms of local, area-averaged and stagnation point Nusselt numbers, respectively. Experimental and numerical correlations are presented for the stagnation point Nusselt number.
PUBLISHED
Keywords: Flow dynamics; Smart & Sustainable Planet; Telecommunications